The role of social entrepreneurship orientation, social capital, and social innovation in Village-Owned Enterprises (VOE) performance: A study in Yogyakarta Province - Widiastuti, Harjanti; Pratama, Muhammad Rizky; Utami, Evy Rahman (Journal of Accounting and Investment, 2024)
Research aims: This study aims to examine the role of social entrepreneurship orientation, social capital, and social innovation in improving Village-Owned Enterprises’ (VOE) performance. Specifically, this study examines social innovation as a moderator of the relationship between social capital and performance.Design/Methodology/Approach: This study used a quantitative approach with primary data types taken using a questionnaire instrument. The data were taken from 199 VOE in Yogyakarta Province. The subjects of this research were the managers of VOE in Yogyakarta Province, including directors, secretaries, treasurers, or heads of business units.Research findings: This study revealed that (1) social entrepreneurship orientation and social capital yielded a positive effect on VOE performance, (2) social innovation did not moderate the relationship between social capital and VOE performance, and (3) social innovation positively affected VOE performance.Theoretical contribution/Originality: VOE has a social mission in its business development. Social innovation should be a concern of VOE in achieving its mission. This research contributes to testing the role of social innovation in VOE performance. Practitioner/Policy implication: VOE, village government, and relevant agencies need to develop programs to improve their social entrepreneurship orientation, social capital, and social innovation, such as training programs and increased collaboration.